Pemahaman Peraturan Pajak, Modernisasi Pelayanan dan Pemahaman “Fatwa Ki Hadjar Dewantara” Ing Ngarsa Sung Tuladha terhadap Kemauan Membayar Pajak Kendaraan Bermotor - Sri Lestari Yuli Prastyatini; Maulidda Aris Mutia (Journal of Management and Bussines (JOMB), 2023)
This research aims to examine the influence of understanding tax regulations, modernization of services and understanding ing ngarsa sung tuladha on the willingness to pay motor vehicle tax. The method in this research uses a sampling technique using snowball sampling. The data analysis used is multiple linear analysis. The research results for each variable have significant values, namely 0.012, 0.000 and 0.004 and t values of 2.553, 4.165 and 2.949. The conclusion is that the variables understanding tax regulations, modernization of tax services and ing ngarsa sung tuladha have a positive effect on the willingness to pay motor vehicle tax. Keywords: Ing Ngarsa Sung Tuladha, Service Modernization, Tax